Structure of abdominal and mandibular exocrine glands in dung beetles (Coleoptera: Scarabaeinae) - Ix Balam, Manuel Alejandro (2018)
Chemical communication is the exchange of information between individ- uals through semiochemicals produced by exocrine glands. The study of the morphology and localization of the exocrine glands is important to un- derstand the chemical communication in insects. Chemical communication plays an important role in dung beetles. However, different morphological aspects of semiochemical producing glands and the chemical nature of se- cretions are still little known. The dung roller beetle Deltochilum furcatum (Scarabaeinae) forms food balls using excrements and carrion, which are rolled to safe sites for feeding or nesting. During the rolling, D. furcatum marks the food ball with semiochemicals that inhibit the oviposition of com- peting flies. However, the origin and chemical composition of the secretions are unknown. Here, we examined the structural and histochemistry organi- zation of exocrine glands associated with the chemical communication of D. furcatum. In the first study, we analyzed regions of the beetle body that are in frequent contact with the food ball during rolling. Also, we proposed a hy- pothetical model that describes the process of production and impregnation of the secretion in the food ball. We have demonstrated that D. furcatum presents bicellular and multicellular exocrine glands in the thorax, abdomen and pygidium. The secretory cell of the gland synthesized protein, lipids, and carbohydrates compounds. The conformation of these exocrine glands in D. furcatum is distinct from that reported in other species of Scarabaeinae. In the second study, we analyzed the mandibles of D. furcatum. Associated with mandibles there are mandibular and intramandibular glands, the latter described by the first time in a dung beetle. The mandibular gland has bicel- lular secretory units connected to a wrinkled reservoir that opens at the base of the mandible. The intramandibular glands were formed of: (I) bicellu- lar secretory units that open directly to the mandible surface; (II) epithelial glands with reservoirs formed of grouped modified epidermal cells forming the coating of an invaginated reservoir where the secretions are stored and released to the mandible surface; and (III) epithelial glands without reservoir that are hypertrophied epidermal cells in the conjunctive and the molar lobe of the mandible, releasing secretions by diffusion through the cuticle. The mandibular and intramandibular glands were rich in proteins and carbohy- drates. The epithelial glands with reservoirs also have lipids. The structural characteristics of these mandibular glands of D. furcatum are similar to those of social insects, such as bees and ants, which have a complex chemical com- munication system.